Exposure to polycyclic aromatic hydrocarbons and assessment of potential risks in preschool children - Oliveira, Marta (2015)
As children represent one of the most vulnerable groups in society, more information concerning their exposure to health hazardous air pollutants in school environments is necessary. Polycyclic aromatic hydrocarbons (PAHs) have been identified as priority air pollutants due to their mutagenic and carcinogenic properties that strongly affect human health. Thus, this work aims to characterize levels of 18 selected PAHs in preschool environment, and to estimate exposure and assess the respective risks for 3–5-year-old children (in comparison with adults). Gaseous PAHs (mean of 44.5 ± 12.3 ng m−3) accounted for 87 % of the total concentration (ΣPAHs) with 3–ringed compounds being the most abundant (66 % of gaseous ΣPAHs). PAHs with 5 rings were the most abundant ones in the particulate phase (PM; mean of 6.89 ± 2.85 ng m−3) being predominantly found in PM1 (78 % particulate ΣPAHs). Overall child exposures to PAHs were not significantly different between older children (4–5 years old) and younger ones (3 years old). Total carcinogenic risks due to particulate-bound PAHs indoors were higher than outdoor ones. The estimated cancer risks of both preschool children and the staff were lower than the United States Environmental Protection Agency (USEPA) threshold of 10−6 but slightly higher than WHO-based guideline.